2023
DOI: 10.3389/fnut.2022.1082976
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between intake of fruits, vegetables and dairy products with overweight and obesity in a large sample in Iran: Findings of STEPS 2016

Abstract: BackgroundThe present study aimed to investigate the association between fruits and vegetables (FVs) and dairy product intake with body weight based on the data from the nationwide Stepwise approach to surveillance (STEPS) survey in Iran.MethodsSTEPS is a national-based cross-sectional study conducted on 3,0541 people selected by stratified cluster random sampling in Iran from April to November 2016. The outcome of the current study was body mass index (BMI) which was classified as normal weight, underweight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
3
1
Order By: Relevance
“…We found an inverse association between recommended fruit and vegetable consumption and multimorbidity, regardless of sex. Evidence suggests that high consumption of fruits and vegetables is a protective factor for several NCDs, such as obesity ( 89 ), ischemic stroke ( 90 ), and diabetes ( 91 ), contrary to our findings. This can be explained by the following factors: (i) information on the recommended fruit and vegetable consumption is self-reported in the NHS.…”
Section: Discussioncontrasting
confidence: 99%
“…We found an inverse association between recommended fruit and vegetable consumption and multimorbidity, regardless of sex. Evidence suggests that high consumption of fruits and vegetables is a protective factor for several NCDs, such as obesity ( 89 ), ischemic stroke ( 90 ), and diabetes ( 91 ), contrary to our findings. This can be explained by the following factors: (i) information on the recommended fruit and vegetable consumption is self-reported in the NHS.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is supported by Jesser and Santoso's 2021 research stating that as many as 84% of the group with obese nutritional status had low vegetable intake 34 . The same results were found in a study by Nouri M et al in 2022, which stated that consumption of vegetables in obese and overweight people was lower when compared to groups with normal nutritional status 35 .…”
Section: E-issn: 2580-1163 (Online) P-issn: 2580-9776 (Print) Risanti...supporting
confidence: 84%
“…The result from the study is inconsistent with previous studies that have found a significant association between FVC and the risk of hypertension (16,17) . However, it is corroborated by some studies that found no significant association between FVC and the risk of hypertension (1,11,23) . The observed nonsignificance of FVC in relation to hypertension risk may reflect the effects of strong confounders, including their level of physical activity, Na intake and cooking practices which could not be accounted for in this study.…”
Section: Discussionmentioning
confidence: 70%